The Paradox of Breadth: The Tension between Experience and Legitimacy in the Transition to Entrepreneurship*. (December 2017) - Kacperczyk, Aleksandra; Younkin, Peter
In a study of artists who launched independent record labels in the music industry from 1990 to 2013, we focus on explaining the paradox generated when prospective entrepreneurs accumulate broad functional experience, which signals to resource providers mastery of different skills and access to various information and resources but may also undermine the legitimacy of their entrepreneurial claims because they are not seen as specialists. To resolve this paradox, we theorize that the potential legitimacy discount of categorical membership can be avoided when individuals are classified according to multiple categories simultaneously. We find that the transition to entrepreneurship is most likely to occur when an artist's functional experience is broad but market experience is narrow: he or she has mastered a variety of skills but solicited few audiences. We also find that the paradox of breadth is attenuated—the potential penalty of functional breadth and the corresponding need to develop narrow market experience are reduced—when the entrepreneur has alternate methods of signaling legitimacy, including high status and more-typical prior work experience. Moreover, some audiences are more disposed than others to allow an entrepreneur to pursue greater novelty. Our findings suggest that mastering a variety of skills is not universally beneficial for aspiring entrepreneurs. In some circumstances, such mastery is best coupled with a narrow market focus.